Hepatoprotective Activity Of Superliv Liquid In Ccl4 Induced Flks Syndrome In Commercial Broilers - Sonkusale, P. M.; Sawarkar, A. R.; Jumde, P. D. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A total of 75 day old broiler chicks were divided into three equal groups. Group A served as negative control. Group B (positive control) and C (treatment group) were intoxicated with CCl4 orally @ 1 ml/kg body weight after every 3rd day during 15-28 days of age. Treatment group C was given superliv liquid @ 10 ml/100 chicks / day in drinking water during 29th-42nd day of age. At the end of experiment, significantly (P
Keywords: CCL4 Toxicity; Superliv; Hepato-protective; Broilers